Penerapan Etika Birokrasi dalam Kualitas Pelayanan Publik KPU Kabupaten Mojokerto - Hikmah Muhaimin; Ghozali, Ghozali; Afida Izzatus Syifa; Revi Firmala Anggraini; Khisamuddin, Khisamuddin (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
Realizing the services needed by the community is the task of bureaucrats who are in the government bureaucracy. Mojokerto Regency as one of the regions in Indonesia also has a duty to provide quality public services to the community. Therefore, the application of bureaucratic Ethics in the quality of public services in the Mojokerto Regency KPU is very important to improve the quality of public services in the area. The purpose of this study was to determine how the application of bureaucratic Ethics in the quality of public services in the Mojokerto Regency Commission. This study uses descriptive qualitative research methods with data collection through observation and interview. The result of this study is that the Mojokerto Regency KPU has made several efforts to implement bureaucratic Ethics in public services. By applying bureaucratic Ethics in public services, the Mojokerto Regency KPU provides better public services and fulfills the rights of the community to obtain quality public services. In addition, these efforts can also increase public confidence in the bureaucracy and local government. Therefore, the application of bureaucratic Ethics in the quality of public services in the Mojokerto Regency KPU is very important to improve the quality of public services in the area.